PENGEMBANGAN EKONOMI SEBAGAI STRATEGI KEAMANAN DI DAERAH PERBATASAN NEGARA: POTENSI DAN TANTANGAN DALAM PENGEMBANGAN PETERNAKAN DI KALIMANTAN BARAT - Gontom Citoro Kifli; Sammy Mochammad Shafar (Jurnal Kawistara, 2019)
Studies on border areas have given much attention on their strategic position in term national security sectors. This security-oriented analaysis overlook economic potential of border areas that are essential in the development of border areas and marginal society. The rich economic potential of border areas evident in the outer areas of Wes Kalimantan, including five regencies which are directly adjacent to the Sarawak state of Malaysia.  Three out of five districts have the official cross-border. These areas have extensive potential land as a source of forage and livestock feed; however the effort to increase animal husbandry and meat production are still met with challenges. The purpose of this study is to analyze the condition of food security of the people at the border, especially in animal protein sufficiency and to make a proper strategy in improving of livestock sector in order of food security at the border areas of West Kalimantan. This study is based quantitative analysis of farming statistic in West Kalimantan. Using Dependency Theory this study found that while people at border are in West Kalimantan are relatively safe from food scarcity, their productivity is lower than the potential in livestock population and meat production. Two factors are essential, namely 1) optimization of superior forage planting on cultivated land and grazing land, and 2) maximum utilization of rubber and palm oil plantation application of integrated crops and livestock system and its modification